A Scheme for Generating Provenance-aware Applications through UML (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The metadata that captures information about the origin of data is referred to as data provenance or data lineage. The provenance of a data item captures information about the processes and source data items that lead to its creation and its current representation. A provenance-aware application captures and stores adequate documentation about process executions to answer queries regarding provenance. Provenance information is very useful when we need to know the inter dependency of data to find error propagation or information flow. Provenance collected also helps to understand what went different in two identical workflows with same inputs but producing different outputs. Currently, most of the provenance systems designed is domain specific. Through this paper, we propose a general methodology for making an application provenance-aware from the basic UML design diagrams. As a starting point we have analyzed UML Class diagrams to generate information to make application provenance aware.